Piper Reed gets a job - Holt, Kimberly Willis (Henry Holt and Co., 2009)
When she discovers the price of the coveted clubhouse, ten-year-old Piper and her fellow Gypsy Club members try to earn the money by creating a birthday-party-planning business.